2004
DOI: 10.1539/joh.46.316
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Vitamin D Receptor Polymorphism Affecting Workers’ Susceptibility to Lead

Abstract: exposure status, smoking and alcohol drinking, were significantly associated with ICL and time-weighted ICL. Regression analyses suggested that exposure status and personal habits (smoking and alcohol drinking) are still the major effects on blood lead parameters for lead workers rather than genotypes. In conclusion, VDR genotypes did not significantly affect the long term blood lead parameters after adjustment for all factors, but industrial hygiene improvement, including engineering control and health educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
1
2
1
Order By: Relevance
“…Very few studies have discussed the influence of VDR-Apa (rs7975232) SNP. A previous study mentioned that higher TWICL was noted for the CC genotype than CA type than AA type in Apa (rs7975232) [27]. A similar trend was also observed in this study, although the difference was not significant.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Very few studies have discussed the influence of VDR-Apa (rs7975232) SNP. A previous study mentioned that higher TWICL was noted for the CC genotype than CA type than AA type in Apa (rs7975232) [27]. A similar trend was also observed in this study, although the difference was not significant.…”
Section: Discussionsupporting
confidence: 86%
“…Chuang et al found that chronically lead-exposed workers had higher blood lead levels and index of cumulative blood lead (ICL) in the Apa AA genotypes. [27] Metallothioneins (MTs) are cysteine-rich, metal-binding, low-molecular-weight proteins [28,29]. MT proteins have multiple functions, such as free radical scavenging and the detoxification of metal(loid)s including cadmium, arsenic, mercury, and lead [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…While a study reported that VDR genotypes do not affect long term BLLs (Chuang et al, 2004); our study shows a relation between various genotypes. This could be either due to sample sizes or because the study was conducted over a short term.…”
Section: Discussioncontrasting
confidence: 58%
“…: NC_000009.12), 22 25 VDR (Vitamin D receptor; Gene ID: 7421; Accession no. : NC_000012.12), 26 –29 G6PD (Glucose-6-phosphate dehydrogenase; Gene ID: 2539; Accession no. : NC_000023.11), HFE (Hemochromatosis; Gene ID: 3077; Accession no.…”
Section: Environmental Response Machinery and Genetic Factors Influen...mentioning
confidence: 99%